1962
DOI: 10.1128/jb.83.5.968-974.1962
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Stability of the Normal Human Fecal Flora

Abstract: Studies on the stability of the normal human fecal flora. J. Bacteriol. 83:968-974. 1962.-The results of two series of stool cultures show that members of the genus Bacteroides constitute the most numerous group of bacteria in the normal human adult fecal flora. Together with the enterococci, coliform bacilli, diphtheroids, and lactobacilli, these major components account for more than 99%7o of the total counts. Wide fluctuations in the number and types of minor organisms observed suggest the probability that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1

Year Published

1968
1968
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 11 publications
4
23
1
Order By: Relevance
“…The results in Tables 1 and 2 show that BFG in faeces and sewage may be enumerated by the membrane filtration technique with either HBGP or WCGP media. The numbers of pBFG isolated from faeces (9.7 x 10'-2.8 x 10y/g wet wt) are similar to those reported by other workers using other methods (Zubrycki & Spaulding 1962;Von Houte & Gibbons 1966;Moore & Holdeman 1974). More pBFG organisms were isolated from crude sewage (1.65 x 1 0 ' 4 8 7 x 106/ml) than were reported by Post et a!.…”
Section: Discussionsupporting
confidence: 88%
“…The results in Tables 1 and 2 show that BFG in faeces and sewage may be enumerated by the membrane filtration technique with either HBGP or WCGP media. The numbers of pBFG isolated from faeces (9.7 x 10'-2.8 x 10y/g wet wt) are similar to those reported by other workers using other methods (Zubrycki & Spaulding 1962;Von Houte & Gibbons 1966;Moore & Holdeman 1974). More pBFG organisms were isolated from crude sewage (1.65 x 1 0 ' 4 8 7 x 106/ml) than were reported by Post et a!.…”
Section: Discussionsupporting
confidence: 88%
“…T h e stability of the numerically-predominant anaerobe populations, such as bacteroides, bifidobacteria and eubacteria reported in this study, is in agreement with previous work (Gorbach et al 1967;Holdeman et al 1976). Furthermore, the variability in populations of Enterobacteriaceae, streptococci and lecithinase-positive clostridia that were observed are similar to early observations which indicated that considerable variation exists with respect to the numbers and types of minor organisms in faeces (Zubrzycki and Spaulding 1962).…”
supporting
confidence: 85%
“…Several studies have been made on the composition of the human colonic microbiota and several investigations have shown that inter-and intra-individual variations of bacterial populations exist (Zubrzycki and Spaulding 1962 ;Holdeman et al 1976;Mitsuoka and Ohno 1977; Meijer-Severs and Van Santen 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported the striking stability of the fecal flora of individual subjects, even when these subjects ingested identical diets (16).…”
Section: Discussionmentioning
confidence: 99%